Desenvolvimento profissional e formação contínua de professores: contribuições do mestrado em educação - Fidelis, Renata Altair (2019)
The research had the objective of analyzing the contributions of the Master’s Program in Education of the Post-Graduation Program in Education of the Federal University of Uberlândia (PGPE/FUU) in the professional development and continuous training of teachers who work in Early Childhood Education and Elementary School of municipal public school system of Uberlândia, Minas Gerais, Brazil, in 2018. In this regard, we considered the following questions: Why do teachers at these levels of education carry out stricto sensu post-graduate programs as a continuous training modality? What are the relations between initial training in undergraduate courses and continuous training in post-graduation? Which changes occur in the teachers’ conceptions, beliefs and knowledge in relation to the pedagogical achievement, while attending the Master’s Program in Education? Are there any significant changes in the teaching career after reaching this title? The investigation is situated in the field of the qualitative approach of educational research, in which public policy documents on teacher training and professionalization, questionnaires and oral interviews with five collaborators were used. The study demonstrated the relevance of stricto sensu post-graduation as a locus of continuous training and professional development.